1989
DOI: 10.1364/ao.28.002043
|View full text |Cite
|
Sign up to set email alerts
|

Elliptical polarization and nonorthogonality of stabilized Zeeman laser output

Abstract: This paper gives both theoretical and experimental proof of elliptical polarization and nonorthogonality of Zeeman laser output. It verifies that the polarized modes of the output have 4-7 degrees orthogonal error which is induced by anisotropy in the laser cavity. A new formula for calculation of this orthogonal error has been derived which also provides a way to measure the anisotropy of the laser cavity. We also discuss the influence of nonorthogonality on the spectrum of the laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Such sources of uncertainty can, if uncorrected, give rise to errors of several nanometres in the accuracy with which measurements can be made. Xie & Wu (1989) developed a theoretical matrix-based analysis of the unwanted elliptical polarization output of a Zeeman-stabilized laser where they concluded that it was due mainly to anisotropy in the laser cavity. Their measurements, using several lasers, showed that the orthogonality errors between the two polarization states were between 4¯and 7¯, which would give rise to errors in length measurement of 3.5 and 6 nm.…”
Section: (A) Heterodyne Interferometersmentioning
confidence: 99%
“…Such sources of uncertainty can, if uncorrected, give rise to errors of several nanometres in the accuracy with which measurements can be made. Xie & Wu (1989) developed a theoretical matrix-based analysis of the unwanted elliptical polarization output of a Zeeman-stabilized laser where they concluded that it was due mainly to anisotropy in the laser cavity. Their measurements, using several lasers, showed that the orthogonality errors between the two polarization states were between 4¯and 7¯, which would give rise to errors in length measurement of 3.5 and 6 nm.…”
Section: (A) Heterodyne Interferometersmentioning
confidence: 99%
“…It has been shown previously that two kinds of non-linearity exist in the Zeeman laser and heterodyne interferometers [12][13][14][15][16], namely errors arising from frequency mixing [16][17][18] and errors from polarization mixing [19]. Frequency mixing errors are the predominant form of non-linear errors in a heterodyne interferometer.…”
Section: Error Analysismentioning
confidence: 99%
“…Periodic errors observed within Zeeman laser heterodyne interferometry have been the subject of much recent discussion [1][2][3][4][5][6][7][8]. Two main approaches to the study of periodic nonlinearity have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…The first utilizes the plane wave representation [1,2,7] whereby the amplitudes of the waves take on broad generalizations in such a way that the influence of individual optical devices is not usually explicit. The second is based on matrix methods [3,5,6,8] whereby not only are the optical properties of the individual components naturally incorporated, but the directionality of the incident electric field vectors of the waves is also considered. Consequently, the latter approach naturally allows for the description of depolarization, birefringence, dichroism, and other similar phenomena associated with the electric field vector.…”
Section: Introductionmentioning
confidence: 99%